PENGEMBANGAN MODUL AJAR BANGUN RUANG BERBASIS LINGKUNGAN DENGAN PENDEKATAN PjBL SISWA KELAS VII - Eli Yana; Venissa Dian Mawarsari; Martyana Prihaswati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Students' geometric thinking skills are still relatively low, because there is a lack of innovation in the learning media used and the learning model used is still not attractive. Students need learning media that can help them improve their geometric thinking skills to be more effective through interactive learning modules. This research aims to develop interactive learning media in the form of a valid environment-based space building teaching module using a project-based learning (PjBL) approach. This research uses the research and development (R&D) method with the ADDIE development model, which is focused on three stages, namely, the analysis stage, the design stage, and the development stage. The results of the study showed that media experts got an average score of 3.26 with a very valid category and material experts got an average score of 3.51 with a very valid category. Overall, the average validation score of the two experts obtained a score of 3.38 with a very valid category. Based on these results, the environment-based building learning module with the PjBL approach meets the feasibility standards and can be piloted on grade VII students of mathematics learning.